COMPARATIVE ANALYSIS OF LAND SURFACE TEMPERATURE BETWEEN OIL PALM PLANTATIONS AND RICE PADDIES IN SOUTHERN SUMATRA ISLAND - Putra, I Kadek Yoga Dwi; K, Muhammad Qabus Abid; P, Cindy Adria A.; Kusratmoko, Eko (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2024)
Land Surface Temperature (LST) is a vital metric for understanding thermal dynamics and environmental impacts of land cover types. Influenced by land use, vegetation, and elevation, LST helps assess ecological changes and human impacts on surface temperatures. This study investigates LST variations between oil palm plantations and rice paddies in southern Sumatra, Indonesia, using Landsat 8 remote sensing data. The aim is to compare the thermal characteristics of these dominant agricultural landscapes across elevation gradients (0–1250 meters above sea level). Results reveal significant LST differences: rice fields generally show higher LST values at lower elevations, while oil palm plantations have elevated LST at mid-elevations. Statistical analyses indicate that, on average, oil palm plantations exhibit a slightly lower LST than rice fields, with a difference of 0.093°C, likely due to higher albedo and reduced evapotranspiration. These findings highlight the complex relationship between land cover and elevation in affecting LST patterns. The insights gained are essential for sustainable land management policies that seek to balance agricultural productivity with environmental conservation. This research deepens our understanding of LST dynamics in agricultural landscapes, providing valuable data for policymakers and land managers.